Cooperative dynamics in two-component out-of-equilibrium systems: molecular 'spinning tops'. (1st December 2022) - Dotsenko, Victor S; Viot, Pascal; Imparato, Alberto; Oshanin, Gleb
Abstract: We study the two-dimensional Langevin dynamics of a mixture of two types of particles that live respectively at two different temperatures. Dynamics is constrained by an optical trap and the dissimilar species interact via a quadratic potential. We realize that the system evolves toward a peculiar non-equilibrium steady-state with a non-zero probability current possessing a non-zero curl. This implies that if the particles were to have a finite-size and therefore a rotational degree of freedom, they would experience a torque generated by the non-zero local curl and spin around their geometric centers, like 'spinning top' toys. Our analysis shows that the spinning motion is correlated and also reveals an emerging cooperative behavior of the spatial components of the probability currents of dissimilar species.